Potential of Perionyx excavatus (Perrier) in lignocellulosic solid waste management and quality vermifertilizer production for soil health - Kasi Parthasarathi; Mariappan Balamurugan; Kottath Valappil Prashija; Lakshmanan Jayanthi; Shaik Ameer Basha (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The aim of this study was to recycle and reuse the enormously available unutilized lignocellulosic solid organic waste resource, cashew leaf litter (CLL) admixed with various animal dungs, cowdung, sheepdung and horsedung by employing predominantly available indigenous epigeic earthwormâPerionyx excavatus (Perrier, 1872) and produce quality vermifertilizer. Methods Four different combinations of each [(100 % dung alone, 3:1 (75 % dung ? 25 % CLL), 2:2 (50 % dung ? 50 % CLL) and 1:3 (25 % dung ? 75 % CLL)] vermibeds were allowed for vermicomposting process under laboratory conditions. After 60 days, the worm worked vermicompost and worm unworked normal compost were harvested and characterized. The earthworm activityâgrowth, reproductive performance (cocoon production and hatchling number) and recovery of vermicompost was also studied. Results The obtained results clearly showed that vermicompost from CLL admixed with cowdung at 2:2 ratio had lower pH, organic carbon, CâN ratio, CâP ratio, lignin, cellulose, hemicellulose and phenol content, and higher nitrogen, phosphorus, potassium dehydrogenase and humic acid content than the raw substrates and worm unworked normal compost. In addition, pronounced and better earthworm activity was found in the above combination. Conclusion Through vermitechnology way of producing agronomic valid vermicompost using natural waste resources like CLL and animal dungs can be used as bioorganic fertilizer. These vermiresources have vast and diversified potential for maintaining sustainable soil health, fertility, productivity, waste degradation, soil reclamation, land restoration practices and environment health.